SOCIOLOGY OF RACE AND ETHNICITY - Ochoa, Gilda L. (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This is an upper division speaking intensive course that focuses on the historical andcontemporary patterns of race and ethnic relations. We will review some of the key sociological perspectives and works on race and ethnicity. As well as assessing authors’ arguments, research methods, findings, and policy implications, we will consider topics such as racial/ethnic identity formation, the interlocking systems of race, ethnicity, class, and gender, whiteness, panethnicity, ethnoviolence, intra-ethnic and cross-racial relations, political activism and possibilities for change.